МАNAGEMENT OF THE RANGE OF GOODS IN RETAIL TRADE - KOCHNOVA, Irina; ONUFRIENKO, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the conditions of strengthening of competition in the consumer market both between the retail trade enterprises, and domestic and foreign trade networks special value is given to the assortment policy of the enterprise. The assortment policy ensures the achievement of the ultimate goals of the enterprise, connects the components of the commercial strategy and achieves the possibility of the most efficient management of resources. That is why the issues of formation, change and forecasting of the range do not lose relevance and require systematic research among other management problems. Assortment management issues require the synthesis of a large amount of information on the activities of the company and its competitors, on the volume and structure of production, prices and conditions of sale, regions and sales network, and so on. Despite the urgency and, consequently, the high level of development of this problem, it can not be considered solved, especially in terms of developing proposals for Ukrainian companies that are not confident enough not only in foreign markets but also in domestic. The article examines the importance and necessity of assortment policy, formulates product policy objectives, determines the influence of assortment product policy on the development of modern enterprises. The integrated requirement for an integrated approach to addressing the formation of the innovative policy principles of product and the implementation of its key functions in the field of trade entrepreneurship in the retail system. A guidance for efficiency increase of development of product policy of enterprises in contemporary market conditions was proposed.